NMR-Driven Identification of Cinnamon Bud and Bark Components With Anti-Aβ Activity - Ciaramelli, Carlotta; Palmioli, Alessandro; Angotti, Irene; Colombo, Laura; De Luigi, Ada; Sala, Gessica; Salmona, Mario; Airoldi, Cristina (Frontiers in Chemistry, 2022)
The anti-Alzheimer disease (AD) activity reported for an aqueous cinnamon bark extract prompted us to investigate and compare the anti-amyloidogenic properties of cinnamon extracts obtained from both bark and bud, the latter being a very little explored matrix. We prepared the extracts with different procedures (alcoholic, hydroalcoholic, or aqueous extractions). An efficient protocol for the rapid analysis of NMR spectra of cinnamon bud and bark extracts was set up, enabling the automatic identification and quantification of metabolites. Moreover, we exploited preparative reverse-phase (RP) chromatography to prepare fractions enriched in polyphenols, further characterized by UPLC-HR-MS. Then, we combined NMR-based molecular recognition studies, atomic force microscopy, and in vitro biochemical and cellular assays to investigate the anti-amyloidogenic activity of our extracts. Both bud and bark extracts showed a potent anti-amyloidogenic activity. Flavanols, particularly procyanidins, and cinnamaldehydes, are the chemical components of cinnamon hindering Aβ peptide on-pathway aggregation and toxicity in a human neuroblastoma SH-SY5Y cell line. Together with the previously reported ability to hinder tau aggregation and filament formation, these data indicate cinnamon polyphenols as natural products possessing multitarget anti-AD activity. Since cinnamon is a spice increasingly present in the human diet, our results support its use to prepare nutraceuticals useful in preventing AD through an active contrast to the biochemical processes that underlie the onset of this disease. Moreover, the structures of cinnamon components responsible for cinnamon anti-AD activities represent molecular templates for designing and synthesizing new anti-amyloidogenic drugs.